ANALYSIS OF THRESHOLD INTENSITY OF LEAF SPOT INFESTATION CAUSED BY CURVULARIA SPP. ON OIL PALM SEEDLINGS - Cameron, Rizky Randal; Yusticia, Stenia Ruski; Afriani, Siti Rakhmi; Febrianni, Astri (Agrisaintifika: Jurnal Ilmu-Ilmu Pertanian, 2025)
Oil palm is a very important crop economically for Indonesia. However, in oil palm nurseries, there is a disease that can interfere with the growth of oil palm seedlings, namely brown spot disease caused by the pathogen Curvularia sp. The purpose of this study was to determine the potential inhibition of oil palm seedling growth by Curvularia at various scoring levels of the intensity of attack of this disease. The method used in this study was a group randomized design with 6 scoring levels as treatments and 5 replicates at 3, 4, 5 and 6 months of age and 10 replicates at 7, 8, 9 and 10 months of age. The scoring levels were grouped into 1 = 0%, 2 = 1-20%, 3 = 20.1-40%, 4 = 40.1-60%, 5 = 60.1-80% and 6 = >80%. The observation parameters of this study were diameter, plant height, and number of leaves. Data were analyzed using anova and further tests using the BNJ test. The results showed the occurrence of growth inhibition at each age of oil palm seedlings both in diameter, height, and number of leaves of oil palm seedlings. However, not all levels of attack showed significant differences. The highest level of inhibition of Curvularia attack at the age of 10 months.